2015
DOI: 10.3402/jev.v4.26883
|View full text |Cite
|
Sign up to set email alerts
|

Serum‐free culture alters the quantity and protein composition of neuroblastoma‐derived extracellular vesicles

Abstract: Extracellular vesicles (EVs) play a significant role in cell–cell communication in numerous physiological processes and pathological conditions, and offer promise as novel biomarkers and therapeutic agents for genetic diseases. Many recent studies have described different molecular mechanisms that contribute to EV biogenesis and release from cells. However, little is known about how external stimuli such as cell culture conditions can affect the quantity and content of EVs. While N2a neuroblastoma cells cultur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
123
2
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 145 publications
(131 citation statements)
references
References 54 publications
(57 reference statements)
4
123
2
2
Order By: Relevance
“…Moreover, careful attention should be paid to experimental conditions involving EV research for reliable and reproducible results. The secretion levels of EVs and protein composition in their cargoes can vary depending on culture medium with or without serum in vitro [44]. Second, although numerous miRNAs have been identified in samples from liver diseases, their functions and roles in liver pathology are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, careful attention should be paid to experimental conditions involving EV research for reliable and reproducible results. The secretion levels of EVs and protein composition in their cargoes can vary depending on culture medium with or without serum in vitro [44]. Second, although numerous miRNAs have been identified in samples from liver diseases, their functions and roles in liver pathology are largely unknown.…”
Section: Discussionmentioning
confidence: 99%
“…By excluding these yield counts, the statistical significance was lost (p = 0.12), but the results still indicate that some of the increase in EV yield can be explained by insufficient EV depletion of FCS or that starved cells secrete less EVs. In contradiction to this, a recently published study by Li et al (2015) reported an increase in EV yield from N2a and SH-SY5Y cells that received serum-free medium during CM production compared to cells that received EV-depleted medium. Although this has not been thoroughly studied experimentally, it can safely be concluded that an abrupt change to serum-free medium does alter the cells and their secretomes (Fig.…”
Section: Cell Stimulationmentioning
confidence: 74%
“…Extracellular vesicles secreted by cells grown in the absence of serum have been shown to differ in protein composition from those secreted by cells grown in the presence of serum [35]. For this reason, and to mimic the conditions under which the phenotype changes had been observed in functional migration and invasion assays, we chose to grow cells in EV-free medium containing 10% FCS.…”
Section: Resultsmentioning
confidence: 99%